1994
DOI: 10.1002/pssa.2211420215
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive barrier in silver phosphate and silver borophosphate glasses

Abstract: Dielectric measurements are carried out on [60Ag20-x B20,-(40x) P20,] glasses in the frequency and temperature range to lo5 Hz and 120 to 400 K, respectively. The observed dielectric data show an interfacial barrier at the metal-glass contact and reveal a barrier relaxation timebarrier width d, = 8.8 nm, and dc conductivity odC z 1.67 x R-' m-' for the [60Ag20-8 B,O,-32 P,O,] glass at room temperature. A capacitive contribution from BPO, and PO, groups in the bulk along with an interfacial layer capacitance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The AC conductivity of ZrTiO4 was found to be strongly depending on frequency. It has been reported that dispersion in the conductivity is a direct evidence for the hopping motions of charge carriers in neighboring lattice imperfections [20][21][22]. At low frequencies, conductivity is found to be very small flat peak supporting space charge polarization.…”
Section: Ac Conductivitymentioning
confidence: 97%
“…The AC conductivity of ZrTiO4 was found to be strongly depending on frequency. It has been reported that dispersion in the conductivity is a direct evidence for the hopping motions of charge carriers in neighboring lattice imperfections [20][21][22]. At low frequencies, conductivity is found to be very small flat peak supporting space charge polarization.…”
Section: Ac Conductivitymentioning
confidence: 97%